2016
DOI: 10.1121/1.4970954
|View full text |Cite
|
Sign up to set email alerts
|

Investigating flow noise on underwater gliders acoustic data

Abstract: Since November 2015, two underwater gliders equipped with external hydrophones were deployed in the South Brazilian Bight in order characterize the area's soundscape. Contrasting to standard fixed mooring systems (where flow noise is generated by currents passing by the hydrophones), gliders are subject to noise generated by its own downward and upward motion, which may compromise soundscape characterizations if not properly evaluated. In order to investigate induced flow noise on the hydrophone and its charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After several evaluations carried out by the PMPAS-BS data processing team, it was concluded that the threshold speed of 13 cm/s would be the upper limit to consider measurements valid for the PMPAS-BS objectives of metrological measurements of the influence of anthropogenic noise on the ocean soundscape. This value is compatible with the value obtained in the article by (dos Santos et al, 2016), where flow noise was evaluated for the drift speed of gliders.…”
Section: Acoustic Signal Data Processing and Qualificationsupporting
confidence: 91%
See 1 more Smart Citation
“…After several evaluations carried out by the PMPAS-BS data processing team, it was concluded that the threshold speed of 13 cm/s would be the upper limit to consider measurements valid for the PMPAS-BS objectives of metrological measurements of the influence of anthropogenic noise on the ocean soundscape. This value is compatible with the value obtained in the article by (dos Santos et al, 2016), where flow noise was evaluated for the drift speed of gliders.…”
Section: Acoustic Signal Data Processing and Qualificationsupporting
confidence: 91%
“…The gliders were preferably launched near E&P blocks to better measure their noise levels, but some trajectories were also planned in areas of low anthropogenic activity to measure the soundscape of different regions. During the quality control of the acoustic data acquired by the gliders, it was found that current noise would affect the acoustic signals if the diving speed was too high (dos Santos et al, 2016). Therefore, it was decided to keep the dive speed lower than 13 cm/s during the descent phase to improve the quality of the measured acoustic data.…”
Section: Mobile Monitoring Componentmentioning
confidence: 99%
“…In shallow water areas, and areas with high and variable current, such as on the continental shelf, the rate of self-noise is higher than off-shelf as the vehicle needs to use the buoyancy pump, altimeter and perform pitch/roll compensation more frequently. In addition, turbulent flow around the hydrophone results in flow noise proportional to the speed of the glider, particularly visible bellow 20 Hz, but likely present in the 5-50 Hz frequency band (dos Santos et al, 2016;Cauchy et al, 2018). This noise increases significantly above approximately 30 cm/s absolute velocity, indicating that for (a) reliable noise measurements at low frequencies (<50 Hz) and (b) high signal-to-noise ratio (SNR) for marine mammal detection at low frequencies, the glider should be operated with a low glide velocity when possible.…”
Section: Background Noisementioning
confidence: 99%
“…They glide quietly through water, without any propulsion noise; they collect hydrographic profiles, from which sound velocity profiles can be calculated (this is important information for modelling sound propagation); raw acoustic data can be accessed after recovery of the glider; they can carry one or several PAM sensors, offering multiple acoustic monitoring possibilities. Flow noise, generated by turbulent water flow around the glider's hull, is of similar magnitude to flow noise observed on moored PAM systems (Erbe et al, 2015;Dos Santos et al, 2016;Fregosi et al, 2020). Ocean gliders have been equipped with custom-built PAM systems and on-board processing capability for near real-time detection of beaked whales (Klinck et al, 2012) and baleen whales (Baumgartner et al, 2013;Baumgartner et al, 2020), demonstrating the opportunity to use PAM gliders as a component of operational whale monitoring observatories.…”
Section: Introductionmentioning
confidence: 88%
“…Slow speed through water (~0.25 m s -1 ) and an optimised streamlined shape lead to reduced flow noise. Flow noise has however been shown to be a possible issue for PAM applications focusing on weak and low frequency (<100 Hz) signals (Dos Santos et al, 2016;Fregosi et al, 2020). It is possible to reduce the glider's speed through water to reduce flow noise, as shown in a recent study (Fregosi et al, 2020).…”
Section: Flow Noisementioning
confidence: 99%